2012
DOI: 10.1002/j.1532-2149.2012.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of μ‐opioid type 1 receptors by microRNA134 in dorsal root ganglion neurons following peripheral inflammation

Abstract: Our present data suggested a model that miR-134 participated in CFA-induced inflammatory pain by balancing the expression of MOR1 in DRGs, which implied that miR-134 may be a potential therapeutic target for the treatment of neuropathic pain including inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…Out of 111 miRNAs, 68% reported earlier and 32% related to the development of tumors of the nervous system and neurodegenerative diseases, few miRNAs, including miR-500, miR-221 and miR-21, relate to CCI-induced NP [79]. In another study miR-134, expression level found inversely related to MOR, the main transcript of μ-opioid receptor (MOR) gene expression [75]. Post inflammatory pain observations included the down-regulation of miR-134 and upregulation of MOR1 in the same tissues.…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 94%
See 1 more Smart Citation
“…Out of 111 miRNAs, 68% reported earlier and 32% related to the development of tumors of the nervous system and neurodegenerative diseases, few miRNAs, including miR-500, miR-221 and miR-21, relate to CCI-induced NP [79]. In another study miR-134, expression level found inversely related to MOR, the main transcript of μ-opioid receptor (MOR) gene expression [75]. Post inflammatory pain observations included the down-regulation of miR-134 and upregulation of MOR1 in the same tissues.…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 94%
“…The expression and function of miRNA in different animal pain models needs to consider due to the challenge of application and delivery of miRNA in vivo, the potential toxic effects of miRNA and future problems in clinical application [74]. Furthermore, an existing model of miR-134 shows a balanced expression of MOR1 in DRGs in CFA-induced inflammatory pain, which implies that miR-134 may be a potential therapeutic target for the treatment of neuropathic pain including inflammation [75].…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 99%
“…[89][90][91][92][93] Some have successfully provided the proof-of concept for a role of specific miRNAs in influencing behavior using rodent models 79,94-96 (Fig. 4).…”
Section: Mirnas and Painmentioning
confidence: 97%
“…This finding strongly suggests the involvement of miRNAs in long-term cortical plasticity following esophageal acid exposure early in life. Here, we review specific miRNAs that have been identified as the regulators of nociceptive activity and highlight their possible association with pain processing in various pain conditions (Table 87, 99,100,101,103,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] ).…”
Section: Icrornas In Visceral Painmentioning
confidence: 99%